The mediating role of independence in the relationship between auditors’ conscientiousness & openness and professional skepticism - Yahya, Febrina; Andi Ina Yustina,; Mahmudah, Hadi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Auditors are encouraged to assess the fraud factor in audit planning, maintain skepticism during the audit, and assess the nature, timing, and extent of the audit procedures. The purpose of this study is to examine conscientiousness and openness to the experience of professional skepticism with independence as a mediating variable. The method used was a survey in a public accounting firm. All hypotheses in this research were supported. Both personalities of conscientiousness and openness to experience have a positive influence on professional skepticism. Thus, auditor independence positively relates to professional skepticism. The results demonstrated that auditor independence partially mediates the relationships of conscientiousness and openness to the experience of professional skepticism. The findings reveal that both personalities stimulate auditor independence, which lead to enhance professional skepticism.